A dedicated revision total knee service: a surgeon's perspective. (June 2019) - Gabor, J. A.; Padilla, J. A.; Feng, J. E.; Anoushiravani, A. A.; Slover, J.; Schwarzkopf, R.
Abstract : Aims: Revision total knee arthroplasty (rTKA) accounts for approximately 5% to 10% of all TKAs. Although the complexity of these procedures is well recognized, few investigators have evaluated the cost and value-added with the implementation of a dedicated revision arthroplasty service. The aim of the present study is to compare and contrast surgeon productivity in several differing models of activity. Materials and Methods: All patients that underwent primary or revision TKA from January 2016 to June 2018 were included as the primary source of data. All rTKA patients were categorized by the number of components revised (e.g. liner exchange, two or more components). Three models were used to assess the potential surgical productivity of a dedicated rTKA service : 1) work relative value unit (RVU) versus mean surgical time; 2) primary TKA with a single operating theatre (OT) versus rTKA with a single OT; and 3) primary TKA with two OTs versus rTKA with a single OT. Results: In total, 4570 procedures were performed: 4128 primary TKAs, 51 TKA liner exchanges, and 391 full rTKAs. Surgical time was significantly different between the primary TKA, liner exchange, and rTKA cohorts (100.6, 97.1, and 141.7 minutes, respectively; p < 0.001). Primary TKA yielded a mean of 7.1% more RVU/min per procedure than rTKA. Our one-OT model demonstrated that primary TKA (n = 4) had a 1.9% RVU/day advantage over rTKA (n = 3). If two OTs are used for primary TKA (n = 6), the outcome strongly favours primary TKA by an added 34.6% RVUs/day. Conclusion: Our results suggest that a dedicated rTKA service would lead to lower surgeon remuneration based on the current RVU paradigm. Revision arthroplasty specialists may need additional or alternative incentives to promote the development of a dedicated revision service. Through such an approach, healthcare organizations could enhance the quality of care provided, but surgeon productivity measures would need to be adjusted to reflect the burden of these cases. Cite this article: Bone Joint J 2019;101-B:675–681.